(3HhGQb GdEdeGY aj GdQO Ydi ef jMQe GdSeGYs - (3CMeO Hf eMeO Hf eMeO Hf CMeO, CHh GdaJhM, eLO GdOjf GdWhSj GdZRGdj,J (B520 (3g` s
(3ChdgG (B:s
(3jbhd YHjOGddg CMeO Hf eMeO GdWhSj SCdfj HYV GdUdMGA Cf CcJH QSGdI aj GdSeGY hahGFOg hTQhWg s
(3BNQgG (B:s
(3hYOe GMJQGe GdYdeGA hGdUdMGA hdfNJe GdcJGH HMeO Gddg hMSf Jhajbg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B147s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B197s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI HOeTb (B(9221) s
Keywords: (3Gdabg GdMfajs